Multiferroic characteristics and microwave absorption properties of La1.5Sr0.5NiO4/BaTiO3 nanocomposites. (1st December 2022) - Thanh, Tran Dang; Lam, Dao Son; Linh, Dinh Chi; Khuyen, Bui Xuan; Manh, Do Hung; Dung, Dang Duc; Thi Dung, Nguyen; Thi Anh Xuan, Chu; Tran, Ngo
Abstract: As-prepared samples of La1.5 Sr0.5 NiO4 (LSNO) and BaTiO3 (BTO) were prepared by ball milling method combined with heat treatment. X-ray diffraction analysis showed the pure phases of LSNO with a tetragonal structure and BTO with a cubic structure. Average crystalline sizes were 15 and 35 nm for the LSNO and BTO samples, respectively. Lattice parameters ​​of LSNO and BTO were almost unchanged after compositing, indicating no diffusion or chemical reaction between them during the compositing process. Adding LSNO to the BTO-based material significantly improved the ferroelectric and ferromagnetic properties, contributing to the enhancement of the electrical polarisation of the composites. These enhancements also boosted the microwave absorption performance of the composites. In detail, 20LSNO/80BTO nanocomposite embedded in acrylic paint could achieve the reflection loss up to −27 dB, meaning 99.8% of the incident microwave being absorbed. This absorber could also reach absorptivity over 60% for almost the whole range of the K u band frequency, which proved that 20LSNO/80BTO nanocomposite could be used as a good microwave absorber for practical applications.